Analysis of Football Referee Performance in Children's League Competitions - Muhamad Faishal Bayhaqi Abidin; Dinar Dinangsit; Encep Sudirjo (Journal of Physical Education Health and Sport, 2026)
Referees play a central role in the organization of football matches, especially in children's competitions at the district level, where the quality of referee leadership affects the development of young talents, sportsmanship, and organizational image. The need for educational communication and match management that matches the characteristics of players demands a young evaluation of referee performance that is specific to the local context. This study aims to analyze the performance level of football referees in the 2026 Bekasi Regency Askab Children's League competition and identify the most dominant aspects of performance and aspects that still need to be improved based on indicators of decision accuracy, match control, physical fitness, communication, and teamwork. This study uses a quantitative approach with a cross-sectional design to get an overview of the performance conditions of the referee at a certain time without special treatment. The subject in this study is the referee who is responsible for the competition, while the assessment is carried out by observers who have competence in the field of refereeing. The instrument used is a referee performance assessment questionnaire with a Likert scale of 1–5 which includes aspects of decision accuracy, match control, physical fitness, communication, and teamwork. The data obtained was analyzed using descriptive statistics in the form of average scores, standard deviations, minimum and maximum scores, with the help of SPSS software. The results of the study showed that the overall performance of referees was in the high category in all aspects measured. The decision accuracy aspect received the highest score of 77.48%, followed by teamwork at 76.68%, physical fitness at 76.58%, match control at 75.56%, and communication at 75.28% as the lowest score, although still in the high category. These findings show that referees have good competence in carrying out their duties during the match. However, the communication aspect still needs to be improved to support the effectiveness of interaction with players and officials and minimize potential conflicts on the field.